(3x+4)(2x+1)
If the question asks you to find roots/solutions:
3x + 4 = 0
3x = -4
x = -1.33333333
2x + 1 = 0
2x = -1
x = -0.5
Answer:
1/√5+√3= 1/√5+√3×√5-√3/√5-√3 = √5-√3/(√5)^2-(√3)^2 {(a+b)(a-b)= (a)^2-(b)^2} =√5-√3/5-3 =√5-√3/2 ans... Do you satisfied to my given answer
Step-by-step explanation:
Answer:
7X
Step-by-step explanation:
4X -6+ 3X +6
Combine like terms
4X + 3X -6 +6
7X +0
7X
Answer:
Factor −6x+30
−6x+30
=6(−x+5)
Step-by-step explanation:
That's all there is
The answer is x=23.......................